IX Century – Socio - Political Situation During The Abbasian Rule (Zien Journal of Social Sciences and Humanities, 2024)
In this article, information about the rulers who ruled the Abbasid state in the 9th century, the political processes that prevailed in the country during this period, social relations and the place of this period in the world civilization is covered based on the sources.